TikTok as a Global Platform Phenomenon: Expansion of ByteDance and Its Impact on Consumer Behavior in Emerging Markets - Bintang Arya Yudha W; Arkaan Naufal Hadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines TikTok as a global platform phenomenon driven by ByteDance's international expansion strategy and analyzes its impact on consumer behavior in emerging markets, with particular focus on Indonesia. Using a qualitative literature review methodology, this research synthesizes findings from nine empirical studies published between 2024 and 2026 to construct a comprehensive understanding of how TikTok's global reach, algorithm-driven content distribution, and social commerce integration are reshaping consumer purchasing patterns, brand awareness formation, and social consumption behavior in developing economies. The findings indicate that TikTok has emerged as the world's largest social media platform by user base, with Indonesia ranking first globally with 194.37 million users as of 2025, and projected global advertising revenue reaching USD 12 billion in 2024. TikTok's penetration into Indonesian consumer markets has produced measurable behavioral transformations: SME businesses adopting TikTok marketing report sales increases of 20-40% (Afriany et al., 2025), social media influence accounts for 39.2% of consumer behavior variance among millennials (Kurniawati, 2024), and TikTok content exposure explains 64.2% of consumptive behavior variance among Generation Z (Husain, 2025). This study further identifies that TikTok's global expansion has introduced a new consumer behavior paradigm characterized by algorithm-mediated discovery, shoppertainment-driven purchase decisions, and emotionally-influenced consumption that differs fundamentally from conventional e-commerce behavior. The study concludes that TikTok represents not merely a social media platform but a global consumer behavior transformation engine that demands new strategic frameworks for businesses competing in emerging markets.